A new polymerase chain reaction/restriction fragment length polymorphism protocol for Plasmodium vivax circumsporozoite protein genotype (VK210, VK247, and P-vivax-like) determination - Alves, Renata Tome [UNESP]; Povoa, Marinete Marins; Goldman, Ira F.; Cavasini, Carlos Eugnio; Baptista Rossit, Andrea Regina; Dantas Machado, Ricardo Luiz (Elsevier B.V., 2007)
For the molecular diagnosis of Plasmodium vivax variants (VK210, VK247, and P. vivax-like) using DNA amplification procedures in the laboratory, the choice of rapid and inexpensive identification products of the 3 different genotypes is an important prerequisite. We report here the standardization of a new polymerase chain reaction/restriction fragment length polymorphism technique to identify the 3 described P. vivax circumsporozoite protein (CSP) variants using amplification of the central immunodominant region of the CSP gene of this protozoan. The simplicity, specificity, and sensitivity of the system described here is important to determine the prevalence and the distribution of infection with these P. vivax genotypes in endemic and nonendemic malaria areas, enabling a better understanding of their phylogeny. (c) 2007 Published by Elsevier B.V.
Keywords: Plasmodium vivax genotypes; PCR/RFLP; diagnosis; circumsporozoite protein; Plasmodium vivax-like; VK210; VK247